PENDAMPINGAN MEMBANGUN SPIRITUAL INTELLIGENCE DI TAMAN PENDIDIKAN DESA KUREKSARI KECAMATAN WARU KABUPATEN SIDOARJO - Soffil Widadah (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
At this time, children have been so much influenced by the glamorous life that they forget about religious lessons. There are also those who have received religious lessons at school but find it difficult to practice because of the lack of parental assistance. This is because parents are busy working. This assistance aims to overcome religious problems in the village of Kureksari Waru Sidoarjo. The activities carried out at TPQ Al Ittihad Kureksari Waru Sidoarjo were carried out in three stages. In the first stage, observations were made on the target of the activity program to determine the method of assistance according to the conditions and situation of the target. In addition, coordination with the head of the Education Park is also carried out for licensing issues as well as preparing various things related to activities. In the second stage, namely the implementation stage, assistance in building spiritual intelligence on the target. At the last stage, evaluation and follow-up activities are carried out in the form of consultation or follow-up guidance for children who want to deepen their spiritual intelligence. Mentoring is done by collaborating on how to build spiritual intelligence with the material of Akidah, Fiqh, Akhlaq, and Islamic History. Evaluation to see the children's consistency in practicing the material in everyday life is done by providing an activity control book that must be filled out every day by the children.